2016
DOI: 10.1038/srep29982
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating pharmacodynamic interaction of silver nanoparticle - topical deliverable antibiotics

Abstract: In order to exploit the potential benefits of antimicrobial combination therapy, we need a better understanding of the circumstances under which pharmacodynamic interactions expected. In this study, Pharmacodynamic interactions between silver nanoparticle (SNP) and topical antibiotics such as Cefazolin (CEF), Mupirocin (MUP), Gentamycin (GEN), Neomycin (NEO), Tetracycline (TET), Vancomycin (VAN) were investigated using the MIC test, Combination assay followed by Fractional Inhibitory concentration Index and Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 18 publications
(19 reference statements)
1
19
0
Order By: Relevance
“…Direct precipitation was used for preparation of zinc oxide nanoparticles by employing Zn (NO 3 ) 2 as a potent precursor and potassium hydroxide as a precipitator. Aqueous solution of 0.2 M zinc nitrate and 0.4 M KOH solution was synthesized at first, then a 0.4 M solution of potassium hydroxide was added slowly to the solution of 0.2 M zinc nitrate stirring at 25 • C, and a precipitate with white color was collected by centrifugation, then dried under a vacuum oven for 4 h at 70 • C [27]. To produce zinc oxide with different sizes of nano crystallite, zinc oxide was annealed for 4 h at various temperatures from 100 to 650 • C. The size and shape of zinc oxide nanoparticles were characterized using SEM, TEM and HRTEM images.…”
Section: Synthesis Of Zinc Oxide Nanostructurementioning
confidence: 99%
“…Direct precipitation was used for preparation of zinc oxide nanoparticles by employing Zn (NO 3 ) 2 as a potent precursor and potassium hydroxide as a precipitator. Aqueous solution of 0.2 M zinc nitrate and 0.4 M KOH solution was synthesized at first, then a 0.4 M solution of potassium hydroxide was added slowly to the solution of 0.2 M zinc nitrate stirring at 25 • C, and a precipitate with white color was collected by centrifugation, then dried under a vacuum oven for 4 h at 70 • C [27]. To produce zinc oxide with different sizes of nano crystallite, zinc oxide was annealed for 4 h at various temperatures from 100 to 650 • C. The size and shape of zinc oxide nanoparticles were characterized using SEM, TEM and HRTEM images.…”
Section: Synthesis Of Zinc Oxide Nanostructurementioning
confidence: 99%
“…The possible mechanism for the synergistic effect was the production of cytotoxic reactive oxygen species light by the visible blue light resulting in thermal destruction of the bacteria and the release of silver ions resulting in the destruction of the cell membrane of the bacterial [ 53 ]. Thirumurugan et al, evaluated the effects of combining silver nanoparticles with antibiotics such as cefazolin, mupirocin, gentamycin, neomycin, tetracycline and vancomycin against Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli [ 54 ]. The synergistic antibacterial effect was proposed to be as a result of Reactive Oxygen Species (ROS) generated membrane cell damage [ 54 ].…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…Thirumurugan et al, evaluated the effects of combining silver nanoparticles with antibiotics such as cefazolin, mupirocin, gentamycin, neomycin, tetracycline and vancomycin against Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli [ 54 ]. The synergistic antibacterial effect was proposed to be as a result of Reactive Oxygen Species (ROS) generated membrane cell damage [ 54 ]. Balaji et al, reported the synergistic effect of cephalexin, an antibiotic conjugated onto silver nanoparticles against E. coli and S. aureus [ 55 ].…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…Nano-scale materials such as silver nanoparticles have emerged as novel antimicrobial agents in combination with existing antibiotics and have shown the most effective antimicrobial activity in vitro 7779. Several recent studies have tested the efficacy of these silver nanoparticles in combination with antibiotics and they have been found to be a novel therapeutic strategy to treat infections caused by multi-drug-resistant organisms 8082. A synergistic effect increasing the antibiotic activity of penicillin combined with silver nanoparticles has been found against S. aureus including MRSA 83–85.…”
Section: Introductionmentioning
confidence: 99%